Pediatric Surgery as an Essential Component of Global Child Health - Ozgediz, Doruk; Langer, Monica; Kisa, Phyllis; Poenaru, Dan (In Seminars in pediatric surgery, 2016)
Recent initiatives in global health have emphasized universal coverage of essential health services. Surgical conditions play a critical role in child health in resource-poor areas. This article discusses (1) the spectrum of pediatric surgical conditions and their treatment; (2) relevance to recent advances in global surgery; (3) challenges to the prioritization of surgical care within child health, and possible solutions; (4) a case example from a resource-poor area (Uganda) illustrating some of these concepts; and (5) important child health initiatives with which surgical services should be integrated. Pediatric surgery providers must lead the effort to prioritize children׳s surgery in health systems development.
Keywords: Global pediatric surgery; Low and middle income countries; Congenital anomalies; Global health disparities; Global child health; Uganda